Systematic review and meta-analysis of the effects of menopause hormone therapy on risk of Alzheimer’s disease and dementia - Nerattini, Matilde; Jett, Steven; Andy, Caroline; Carlton, Caroline; Zarate, Camila; Boneu, Camila; Battista, Michael; Pahlajani, Silky; Loeb-Zeitlin, Susan; Havryulik, Yelena; Williams, Schantel; Christos, Paul; et al. (Frontiers in Aging Neuroscience, 2023)
Despite a large preclinical literature demonstrating neuroprotective effects of estrogen, use of menopausal hormone therapy (HT) for Alzheimer's disease (AD) risk reduction has been controversial. Herein, we conducted a systematic review and meta-analysis of HT effects on AD and dementia risk. Our systematic search yielded 6 RCT reports (21,065 treated and 20,997 placebo participants) and 45 observational reports (768,866 patient cases and 5.5 million controls). We used fixed and random effect meta-analysis to derive pooled relative risk (RR) and 95% confidence intervals (C.I.) from these studies. Randomized controlled trials conducted in postmenopausal women ages 65 and older show an increased risk of dementia with HT use compared with placebo [RR = 1.38, 95% C.I. 1.16-1.64, P < 0.001], driven by estrogen-plus-progestogen therapy (EPT) [RR = 1.64, 95% C.I. 1.20- 2.25, P = 0.002] and no significant effects of estrogen-only therapy (ET) [RR = 1.19, 95% C.I. 0.92-1.54, P = 0.18]. Conversely, observational studies indicate a reduced risk of AD [RR = 0.78, 95% C.I. 0.64–0.95, P = 0.013] and all-cause dementia [RR = 0.81, 95% C.I. 0.70–0.94, P = 0.007] with HT use, with protective effects noted with ET [RR = 0.86, 95% C.I. 0.77–0.95, P = 0.002] but not with EPT [RR = 0.910, 95% C.I. 0.775–1.069, P = 0.251]. Stratified analysis of pooled estimates indicates a 32% reduced risk of dementia with midlife ET [RR = 0.685, 95% C.I. 0.513-0.915, P = 0.010] and non-significant reductions with midlife EPT [RR = 0.775, 95% C.I. 0.474-1.266, P = 0.309]. Late-life HT use was associated with increased risk, albeit not significant [EPT: RR = 1.323, 95% C.I. 0.979-1.789, P = 0.069; ET: RR = 1.066, 95% C.I. 0.996-1.140, P = 0.066]. These findings support renewed research interest in evaluating midlife estrogen therapy for AD risk reduction.